Activity Budget of Ex-captive Sumatran Orangutan Post Release in Sumatran Orangutan Reintroduction Centre in Jambi - Julius Paolo Siregar; Ani Mardiastuti; Rondang Sumurung Edonita Siregar (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
Excaptive orangutans were not have a proportional activity budget for their suitable food, so that many individuals have been failed to adapt.Assessment daily activity budget should to have for excaptive orangutans to determine successful adaptation to independent life. Our reserachconducted on 13 individuals who were divided into two groups according to behavioral characteristic were seven individuals tame and six individualssemiwild. We recorded their activities for 9-10 days (7.290–8.100 minutes) after their released via instantaneous sampling method with a sampleinterval for 2 minutes. The results showed that group of semiwild spent duration on feeding (43%) higher than tame (28%), whereas tame spent onresting (55%) higher than semiwild (38%). Results of analysis on daily activities of two groups showed significant differences in resting, feeding andother activities among the two groups (n1=70; n2=56) have probability value of Mann Whitney Test resting: p=0,000<0,05; feeding:p=0,000<0,05; other activities: p=0,009<0,05. Only moving activity showed no significant difference results (n1= 70, n2=56; p=0,507>0,05).Semiwild group has activity budget similar to wild orangutans in natural habitat.Keywords: activity budget, ex-captive, sumatran orangutan